THE EFFECT OF LOCAL GOVERNMENT BUDGET CAPACITY ON COVID-19 CASES HANDLING - Ika Kurnia Indriani (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2022)
The COVID-19 pandemic has had a major impact on financial conditions of local government. This study aims to analyze effect of budget capacity on COVID-19 cases in district government of Kalimantan. The research objective to shown the effect PAD, DAK, capital expenditure, and operational expenditure on COVID-19 case. This study uses a descriptive quantitative approach. The results showed that H1 was accepted with sig. <0,001 of district government's budget capacity has a simultaneous effect on COVID-19 cases. H3 is accepted with sig <0,001 that DAK has a partial effect on COVID-19 cases. H4 is accepted with sig. <0,001 that capital expenditure has a partial effect on COVID-19 cases. H5 is accepted with sig. <0,001 that operational expenditures have a partial effect on cases of COVID-19. While H2 is rejected with a sig. 0,388 that PAD have not partial effect on cases of COVID-19 . The highest budget capacity is Kutai Kartanegara, while Taha Tidung has the lowest capacity. The recommendation district government of Kalimantan need to maintain the budget capacity to handling unconditional condition COVID-19 pandemic. Key Words: Budget Capacity, COVID-19, District, and Kalimantan.